Effect of honeybee queen size and HSP90 and HSC70 gene expression on thermal stress resistance - Derafsh, Alireza; Salehi, Abdolreza; Amiri, Esmaeil; Bakhtiarizadeh, Mohammad Reza (Frontiers in Bee Science, 2025)
IntroductionIn beekeeping, queen cell size is a critical factor influencing the growth and development of queen bees. It was hypothesized that larger queen cells would produce queens with greater weight, enhanced resilience to heat stress, and higher expression of heat shock proteins (HSP90 and HSC70), leading to improved survival under environmental stress.Materials and methodsThis study, conducted in Shiraz Province, Iran, in 2023, aimed to test this hypothesis. A total of 270 queens were divided into three groups based on queen cell size: large (10–9.5 mm), medium (9–8.5 mm), and small (7.5–7 mm). The queens were reared using three different methods: 1) simultaneous starter_finisher colonies, 2) separate starter_finisher colonies, and 3) rearing in the presence of the queen. Since there were three different cell types, this resulted in a total of 90 cells for each rearing method. Each group of 90 cells consisted of three subsets of 30 cells: large, small, and medium. From 270 cells, 176 survived and 94 queens died.Results and discussionWe conducted a stepwise procedure using a logistic model, and the results indicated that the model, which included cell type, rearing method, and birth weight, showed the best predictive performance. This was evidenced by the lowest Akaike information criterion value. Then, from rearing method 2, we placed 12 queens of each cell type in two groups of six each subjected to two different stress levels: a low temperature of 4°C and a high temperature above 40°C. A total of 36 frozen queen samples with six replicates for each treatment combination were used for molecular testing. Gene expression analysis was conducted using real-time PCR to evaluate HSP90 and HSC70 gene expression. Results showed that queens produced in larger cells had significantly higher weight, enhanced resilience to heat stress, and higher gene expression of HSP90. These queens demonstrated superior survival rates under high-temperature conditions compared to queens from smaller cells.ConclusionsThe findings support the hypothesis that optimizing queen cell size can enhance queen performance and colony resilience. Our results suggest that larger cells promote improved development, heat stress resilience, and higher survival rates, ultimately improving colony health and productivity.